1989
DOI: 10.1080/00207594.1989.10600060
|View full text |Cite
|
Sign up to set email alerts
|

Male Acceptance of Affirmative Action Programs for Women: The Results of Altruistic or Egoistical Motives?

Abstract: It has been argued in the past that self-interest plays an important role in the reaction of men to affirmative action programs that are designed to promote women in non-traditional jobs. In the main, this hypothesis has received limited support apparently because the conception of self-interest was understood in terms of one's private well-being. It is clear, however, that self-interest also refers to group status or position in society. In this study self-interest was measured through the concept of collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 24 publications
1
41
0
1
Order By: Relevance
“…Research has also shown that support for employment equity programs is strongest when it involves elimination of discrimination (i.e., extending fair treatment to others, Beaton and Tougas, 2001;Veilleux and Tougas, 1989), less support when it emphasized recruitment and training (Kravitz and Platania, 1993), and clear opposition when it involves preferential treatment (Bobocel et al, 1998;Son Hing et al, 2002). Kravitz and Klineberg (2000) have shown that people react to different types of affirmative action policies, depending on the perceived fairness of the affirmative action practices.…”
Section: Support For Employment Equitymentioning
confidence: 95%
See 1 more Smart Citation
“…Research has also shown that support for employment equity programs is strongest when it involves elimination of discrimination (i.e., extending fair treatment to others, Beaton and Tougas, 2001;Veilleux and Tougas, 1989), less support when it emphasized recruitment and training (Kravitz and Platania, 1993), and clear opposition when it involves preferential treatment (Bobocel et al, 1998;Son Hing et al, 2002). Kravitz and Klineberg (2000) have shown that people react to different types of affirmative action policies, depending on the perceived fairness of the affirmative action practices.…”
Section: Support For Employment Equitymentioning
confidence: 95%
“…For example, Tougas and colleagues (Tougas et al, 1991;Veilleux and Tougas, 1989) found support for affirmative action on gender inequalities from both women and men. On the other hand, Fletcher and Chalmers (1991) found low levels of support for employment equity among Canadian citizens, organizational decision makers, and lawmakers.…”
mentioning
confidence: 94%
“…Members of advantaged groups who feel that their status position is insecure may perceive that exclusionary measures are more fair than group members who feel secure (Platow, Wenzel, & Nolan, 2003;Tyler & Smith, 1999;Veilleux & Tougas, 1989). Advantaged group members may also selectively perceive fairness to legitimize their status, either consciously (e.g.…”
Section: The Role Of Fairnessmentioning
confidence: 96%
“…Just as feelings of injustice may motivate participation in collective rebellion and riots (Crawford and Naditch, 1970;Gurr, 1970;Sears and McConahay, 1970), feelings of injustice also may motivate support for constructive and pro-active political attitudes and behaviours (Veilleux and Tougas, 1989). In fact, the recognition of injustice might motivate the advantaged to support policies designed to achieve justice before the disadvantaged pursue the often devastating alternative of collective violence or rebellion, just as, in experiments, it leads people to forego advantages they could obtain Spitzer, 1982, 1985;Kahneman, Knetsch and Thaler, 1986).…”
Section: Study 1: the Advantagedmentioning
confidence: 98%